Serum proBDNF Is Associated With Changes in the Ketone Body β-Hydroxybutyrate and Shows Superior Repeatability Over Mature BDNF: Secondary Outcomes From a Cross-Over Trial in Healthy Older Adults - Norgren, Jakob; Daniilidou, Makrina; Kåreholt, Ingemar; Sindi, Shireen; Akenine, Ulrika; Nordin, Karin; Rosenborg, Staffan; Ngandu, Tiia; Kivipelto, Miia; Sandebring-Matton, Anna (Frontiers in Aging Neuroscience, 2021)
Background: Beta-hydroxybutyrate (BHB) can upregulate brain-derived neurotrophic factor (BDNF) in mice, but little is known about the associations between BHB and BDNF in humans. The primary aim here was to investigate whether ketosis (i.e. raised BHB levels), induced by a ketogenic supplement, influences serum levels of mature BDNF (mBDNF) and its precursor proBDNF in healthy older adults. A secondary aim was to determine the intra-individual stability (repeatability) of those biomarkers, measured as intra-class correlation coefficients (ICC). Method: Three of the arms in a 6-arm randomized cross-over trial were used for the current sub-study. Fifteen healthy volunteers, 65-75 y, 53% women, were tested once a week. Test oils, mixed in coffee and cream, were ingested after a 12-h fast. Labeled by their level of ketosis, the arms provided: sunflower oil (lowK); coconut oil (midK); caprylic acid + coconut oil (highK). Repeated blood samples were collected for 4 hours after ingestion. Serum BDNF levels were analyzed for changes from baseline to 1, 2 and 4 hours to compare the arms. Individual associations between BHB and BDNF were analyzed cross-sectionally and for a delayed response (changes in BHB 0-2 h to changes in BDNF at 0-4 h). ICC estimates were calculated from baseline levels from the three study days. Results: proBDNF increased more in highK versus lowK between 0 and 4 h (z-score: beta=0.25, 95% CI 0.07–0.44; p=0.007). Individual change in BHB 0-2 h, predicted change in proBDNF 0-4 h, (beta=0.40, CI 0.12–0.67; p=0.006). Change in mBDNF was lower in highK versus lowK at 0-2 h (beta=–0.88, CI –1.37 to –0.40; p<0.001) and cumulatively 0-4 h (beta=–1.01, CI –1.75 to –0.27; p=0.01), but this could not be predicted by BHB levels. ICC was 0.96 (95% CI 0.92–0.99) for proBDNF, and 0.72 (CI 0.47–0.89) for mBDNF. Conclusions: The findings support a link between changes in peripheral BHB and proBDNF in healthy older adults. For mBDNF, changes differed between arms but independent to BHB levels. Replication is warranted due to the small sample. Excellent repeatability encourages future investigations on proBDNF as a predictor of brain health. Trial Registration: ClinicalTrials.gov, NCT03904433.